sum: m + n = -b/a product: mn = c/a substitute. when proving, you only manipulate/solve one side. mnb^2=(m+n)^2 ac (c/a)(b^2) =? (ac)(m+n)^2 (c/a)[a(m + n)]^2 =? (ac)(m+n)^2 (c/a)(a^2)(m+n)^2 =? (ac)(m+n)^2 (ac)(m+n)^2 = (ac)(m+n)^2 this problem is pretty much the same as the ...
Because of the wind, a boat sails 4 728 meters in the directions S 47 degrees 29 minutes W. How far south has it gone? How far west has it gone?
From a mountain 1780 ft. high, the angle of depression of a point on the nearer shore of a river is 48 degrees 40 minutes and of a point directly across on the opposite side is 22 degrees 20 minutes. What is the width of the river between the two points?
From a lookout tower 80 ft. high, a man observes from a position 6.5 ft. below the top of the tower that the angle of elevation of the top of a certain tree is 12 degrees 40 minutes and the angle of depression of its base is 72 degrees 20 minutes. If the base of the tower and ...